Analysis of the Relationship Between Providing Drug Information, Medication Adherence, and Glycemic Control in Type 2 Diabetes Outpatients at the North Denpasar Health Center - Pande Made Desy Ratnasari; Agustina Nila Yuliawati; Anak Agung Ngurah Putra Riana Prasetya; Ni Luh Koming Krisnamahesswari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Medication adherence among patients with type 2 diabetes mellitus (T2DM) continues to be a difficult challenge. Providing drug information (PDI) at health centers can enhance medication adherence and help patients achieve glycemic control. A cross-sectional study was conducted in February-April 2024 at the North Denpasar Health Center. Inclusion criteria were patients 18 years old either with or without comorbidities, receiving the same antidiabetic treatment for ≥3 months. Exclusion criteria were patients who withdrew from the study, changed their care, or had unstable health conditions. Medication adherence data were collected using the Probabilistic Medication Adherence Scale (ProMAS) questionnaire, PDI data and fasting blood glucose (FBS) examination results in medical records using data collection documents. Correlation analysis between PDI and medication adherence and glycemic control used the Kendall's tau-b/c test. Results showed patients were mostly male (53.84%), age ≥65 (43.20%), elementary school education (35.50%), unemployed (63.90%), no family history (70.41%), disease duration 5 years (62.72%), with comorbidities (65.09%), and FBS achieved (81.66%). The antidiabetic used was a combination of metformin and glimepiride (54.43%). A total of 81.65% obtained routine PDI with high medication adherence (48.52%). The conclusion of the study was that there was a significant relationship between PDI with medication adherence (p=0.000; r=0.253) and glycemic control (p=0.000; r=0.447).